Princeless. Volume 9, Love yourself - Whitley, Jeremy (Action Lab Comics, 2019)
The end of her quest is in sight as Adrienne has one last sister to save. To do so, she will have to navigate a maze, guarded by a Minotaur, devised and run by her own father. Meanwhile, in the faraway woods of the elves, Devin, Kira, Noni, and Tempest have been captured, and the only one with a chance at saving their skins is Tempest.